Clinical Significance of Nontuberculous Mycobacteria Isolated From Respiratory Specimens in a Chinese Tuberculosis Tertiary Care Center - Duan, Hongfei (Sci Rep, 2016)
The clinical relevance of non-tuberculous mycobacteria (NTM) has been reported to be different dramatically by species or by regions, however, no such evaluation has been performed in China.A retrospective study was performed in Beijing Chest Hospital. All the NTM strains isolated from respiratory specimens in the past 5 years, and patients’ clinical records (symptoms and radiographic information etc.) were investigated. The clinical relevance was evaluated according to the criteria recommended by the American Thoracic society. Totally 232 NTM strains were recruited, among them, M. intracellulare was the dominant species (40.5%), followed by M. abscessus (28.4%). 109 patients, with 185 total isolates, had full clinical records available for review. 84.4% (38/45), 85.7% (24/28%) and 63.6% (7/11) of patients with isolation of M. intracellulare, M. abscessus and M. kansasii, respectively, were categorized as definite NTM disease. Whereas all the 10 patients with isolation of M. gordonae were defined as unlikely NTM disease. The majority of NTMs isolates yielded from respiratory specimens in Beijing Chest Hospital were clinically significant, and M. intracellulare and M. abscessus was the dominated species of NTM lung disease. NTM lung infections demonstrated some specific chest radiograph characteristics.